Effectiveness of Educational Intervention with non-wax and Virtual Typodont Methods in Practical Orthodontic course of Dental Students, Shahid Beheshti University of Medical Sciences - Mirmoghtadaie, Zohrehsadat; Seifi, Massoud; Namdari, Mahshid; Eskandarloo, Fatemeh; Amdjadi, Parisa (Journal of Dental School, 2023)
Objectives Considering the educational value of non-wax and virtual typodonts, in this study, the results of the evaluation were compared to quantify each of the indicators in the evaluation of knowledge, attitude, and performance. Methods All tenth-semester dental students were divided into 2 equal groups of 25 and were trained by two typodontists. A standard questionnaire with a Cronbach α of .830 was used to evaluate their knowledge and attitude, which was prepared based on a 7-point Likert scale. To analyze the data, the paired t test, independent t test, and analysis of covariance (ANOVA) were used with SPSS version 21. The significance level was set as 0.05. Results In each of the 2 educational methods, a significant increase in the overall score of the questionnaire completed by the students was observed after the educational intervention (P < 0.001). Among the 17 questions related to students, only 1 question in the non-wax typodont group and 4 in the virtual typodont group did not show a significant effect of the intervention (P > 0.05). Conclusion Both typodonts had remarkable educational advantages and accounted for a large share of the points in the questionnaires. In cases where physical sense was important in education, non-wax typodont and in cases where spatial understanding of biomechanics was necessary in tooth movement, virtual typodont was superior.